2015
DOI: 10.1515/zpch-2015-0665
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism in Cu Resonant Auger Electron Diffraction

Abstract: Upon a core level excitation by circularly polarized light (CPL), the angular momentum of light, i.e. helicity, is transferred to the emitted photoelectron. This phenomenon can be confirmed by the parallax shift measurement of the forward focusing peak (FFP) direction in a stereograph of the atomic arrangement. The angular momentum of the emitted photoelectron is the sum of CPL helicity and the magnetic quantum number (MQN) of the initial state that define the quantum number of the core hole final state. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The polar angle (θ ) dependences of p to d and d to f transition probabilities were calculated and shown elsewhere [22]. spiral [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polar angle (θ ) dependences of p to d and d to f transition probabilities were calculated and shown elsewhere [22]. spiral [30].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a prominent FFP ACD was also found in the Auger electron intensity angular distribution at the absorption threshold [20][21][22]. Extraordinary large angular momentum transfer to the resonant Auger electron where the excited core electron is trapped at conduction-band state was found by Morscher et al [20] for Ni L 2 absorption and showed that the surface magnetization orientation can be determined in three dimensions.…”
Section: Core-level Photoelectron Diffraction Is a Powerful Techniquementioning
confidence: 89%
See 1 more Smart Citation